Analisis Dampak Atraksi Sektor Wisata Terhadap Ekonomi, Budaya Dan Lingkungan Sekitar Kawasan Museum Sribaduga, Bandung - Kurnia, Ratu; Ramdani, Dadan (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the impact of the Sri Baduga Museum's tourism sector on the economic, cultural, and environmental aspects of the surrounding community, particularly in the Tegallega area of Bandung City. As a cultural tourism destination in West Java, the Sri Baduga Museum not only serves as a place to preserve Sundanese history but also contributes to stimulating the local economy, strengthening cultural identity, and supporting environmental sustainability. This study used a descriptive qualitative approach using in-depth interviews and observations with various stakeholders, including tourists, local vendors, and museum management. The results indicate that the Sri Baduga Museum has a positive impact on three main aspects. These impacts are due to the appropriate management of funds for maintenance and sustainable tourism development. Economically, the museum's presence encourages micro-business activity around the tourist site. Culturally, the museum serves as an interactive educational platform, enriching the younger generation's understanding of local history and culture. Environmentally, the museum maintains a beautiful and clean area, although increased visitor awareness of cleanliness is still needed. Overall, the museum serves not only as a center for historical information but also plays a vital role in sustainable urban development. This study recommends increasing promotion, strengthening collaboration between museums and local economic actors, and utilizing digital technology to attract the younger generation.